Pengaruh Terpaan Konten Instagram @pemimpin.indonesia terhadap Sikap Kepemimpinan Positif pada Followers - Aisah, Nur; Sutarso, Joko (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2025)
Advances in technology and social media have opened up vast opportunities for individuals and organizations to participate in media content production. However, research on the influence of social media on the formation of leadership attitudes is still minimal, especially in the context of the use of leadership accounts on Instagram. This study aims to determine whether there is an influence of the content published through the Instagram account @pemimpin.indonesia on the leadership attitudes of its followers and to measure the extent of this influence. The study uses the SOR (stimulus-organism-response) theory as the basis for testing the research. The research approach used is quantitative, with purposive sampling as the sampling technique. The Slovin formula was applied to calculate the research sample. Based on the calculations, 100 respondents who follow the @pemimpin.indonesia account were obtained. The R-square coefficient test result was 71.4%, while the remaining 28.6% was influenced by other variables. The regression test showed that the value Y = 9.133 + 0.683 X had a positive value between variables. Recommendations that can be used as a reference for further research include comparing the influence of other leadership accounts on Instagram or utilizing other platforms such as TikTok, which also provide similar content. This step aims to assess how effective the media is in conveying information that can motivate leadership.